(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This work has researched the recombination processes that occur in semiconductors and its effect on the lifetime of charge carriers. It has been shown that the rate of recombination under external influence depends on the concentration of non-balanced charge carriers. It has been argued that the recombination rate of interbranch radiation is greater in straight-zone semiconductors than in faulty-zone semiconductors, and that the lifetime of electrons and cavities is much larger in straight-zone semiconductors. The reasons why the lifetime of non-primary charge carriers increases with increasing temperature are explained.